GAMBARAN FAKTOR PENGHAMBAT DALAM PELAKSANAAN PEMBELAJARAN DARING PADA MAHASISWA FAKULTAS KEPERAWATAN UNIVERSITAS RIAU - Vivi Dwiyani; Herlina Herlina; Nopriadi Nopriadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Online learning is learning activities by utilizing the internet as a method of interaction in learning. Inhibiting factors in the implementation of online learning can be classified into internal and external factors. This study aim to describes the inhibiting factors in implementing online learning for nursing students in the Faculty of Nursing, Riau University. This research is quantitative research with a descriptive design. The sample in this study was 242 respondents using the probability sampling technique with a simple random type. The measuring instrument used was a questionnaire inhibiting factor in the implementation of online learning. The results showed that the majority of students had good physical conditions with a total of 138 respondents (57,0%), good psychological conditions with a total of 192 respondents (79,%), in terms of good educators with a total of162 respondents (66,9% ), good facilities with a total of 127 respondents (52.5%), families who are good at supporting online learning, with a total of 190 respondents (78,5%), and other activities that are good with a total of 162 respondents (66,9%). This research is expected to be used as a reference and source of information to describe the inhibiting factors in implementing online learning. Keywords: Inhibiting factors, students, online learning.